The Influence Of Self-Efficacy On Students' Interpersonal Communication In Higher Education - Maulidya Amhar Amin Lar; Sukardi Weda; Sidirman Maca (Postgraduate Bosowa University, 2023)
The objectives of this study explored two main cases, (1) what is the influence of self-efficacy on students' interpersonal communication in higher education and (2) What was the level of self-efficacy on interpersonal communication in higher education. This study applied mixed method which is explanatory sequential design or well-known as QUAN-QUAL as the one of the types of mixed method research. There was one class of the third semester students participated as the participant and this study conducted in Universitas Muslim Indonesia. The result of this research leads to the evidence that self-efficacy influence on interpersonal communication. There were three the influence of self-efficacy on interpersonal communication they are confident, motivation and self-control. Students who have high self-efficacy toward interpersonal communication tend easier to speak up than the students who have low self-efficacy. And there are three levels of selfefficacy on interpersonal communication which were experienced by the students. Those three levels covered such categorization such as low self-efficaci obtained 6.1% (two students), moderate self-efficacy obtained 39.4% (thirteen students), and high self-efficacy obtained 54.5% (eighteen students). From these results, the researcher concludes that the level of self-efficacy on interpersonal communication of students is dominantly high with the percent of 54.5%.